Accommodating International Human Rights Law Principles in the Judicial System: Prospective Development of Bangladeshi Domestic Courts - Mohammad Minhazur Rahman (Law and Society Students' Journal)
The unambiguous incorporation of international human rights into many national constitutions demonstrates that legal systems throughout the world are becoming increasingly open to customary international law. Although there is still much disagreement on the "universality" of human rights, most courts across the globe accept the more easily defendable IHRL principles, such as the right to life and freedom and the prohibition of torture. The propensity of national courts, especially in dualist systems like Bangladesh's, to view international human rights legislation as being purely ‘inspirational’ or ‘persuasive’ remains, despite the fact that international law-based judicial thought and activity appear to be on the rise. This paper puts out this argument against the background of recent developments in the use of IHRL principles in Bangladeshi courts. The paper also attempts to evaluate the judicial standpoint, both progressive and conservative, in referencing IHRL by briefly referencing prevailing theories impacting the domestic implementation of international law, discussing the status of IHRL in the Constitution of Bangladesh, and looking at relevant case law.